Papillomatosis cutis lymphostatica and 'Ski‐Jump' nails. Issue 1 (18th November 2020) - Mintoff, Dillon; Betts, Alexandra; Aquilina, Susan
Abstract: Papillomatosis cutis lymphostatica is an uncommon condition usually associated with lymphedema. "Ski‐jump" nails are upward sloping concave nails that can be an important diagnostic sign which may be overlooked in the setting of lymphedema. A diagnosis of papillomatosis cutis lymphostatica should be suspected in patients presenting with persistent, bland papilliform plaques, supported by the additional presence of "ski‐jump" nails.